An Immunosuppressive Tick Salivary Gland Protein DsCystatin Interferes With Toll-Like Receptor Signaling by Downregulating TRAF6 - Sun, Ta; Wang, Fanqi; Pan, Wen; Wu, Qihan; Wang, Jingwen; Dai, Jianfeng (Frontiers in Immunology, 2018)
Ticks, blood-feeding arthropods, secrete immunosuppressive molecules that inhibit host immune responses and provide survival advantages to pathogens. In this study, we characterized the immunosuppressive function of a novel tick salivary protein, DsCystatin, from Dermacentor silvarum of China. DsCystatin directly interacted with human Cathepsins L and B, and inhibited their enzymatic activities. DsCystatin impaired the expression of inflammatory cytokines such as IL1β, IFNγ, TNFα and IL6 from mouse bone marrow derived macrophages (BMDMs) that had been stimulated with LPS or Borrelia burgdorferi (B. burgdorferi). Consistently, DsCystatin inhibited the activation of mouse BMDMs and bone marrow derived dendritic cells (BMDCs) by downregulating the surface expression of CD80 and CD86. Mechanically, DsCystatin inhibited LPS or B. burgdorferi induced NFκB activation. For the first time, we identified that DsCystatin attenuated TLR4 signaling by targeting TRAF6. DsCystatin enhanced LPS induced autophagy, mediated TRAF6 degradation via an autophagy dependent manner, thereby impeded the downstream phosphorylation of IκBα and the nuclear transport of NFκB. Finally, DsCystatin relieved the joint inflammation in B. burgdorferi or Complete Freund's adjuvant induced mouse arthritis models. These data suggested that DsCystatin is a novel immunosuppressive protein and can potentially be used in the treatment of inflammatory diseases.